Effectiveness of reading license technique on reading comprehension and speed among EFL students - Abduljalil Hazaea; Wagdi Bin-Hady (Australian Journal of Applied Linguistics)
In exam-oriented English as foreign language (EFL) foundation programs, achieving a balance between high-stakes testing and skill-based learning remains a challenge. This study addresses the limited efficacy of timed reading activities (TRAs) in such a context, where students prioritize test preparation over fluency-building practices. In line with the license fashion of today, we provide a reading license as a bait to attract EFL students’ attention to TRAs manifested in the Reading Power 1 textbook. In so doing, we aligned the processes of TRAs with those of getting a driving license. Accordingly, this study examines the effectiveness of reading license technique on reading comprehension and reading speed among EFL students. Using experimental research design, 85 students were recruited in this study. The study oriented the students on the processes of getting a reading license. With these students, the first author used the reading license technique for one semester during which reading speed and reading comprehension were scaffolded with high-stake tests. Then, five TRAs, with a corpus of 2000 words, were used to examine the comprehension level and reading speed among the students using the reading license technique to teach TRAs. The results showed that students achieved good scores (mean=3.16 out of 5) and high reading speed (173.29 words per minute) using this technique. The results recommend that investing students’ background knowledge such as the processes of getting a driving license with TRAs is a great scaffolding strategy to motivate students and enhance reading comprehension and reading speed. This study contributes to teaching techniques for timed reading activities in the context of high-stakes tests.